2017
DOI: 10.1038/ncomms15864
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 7 and its adaptors link cadherins to actin

Abstract: Cadherin linkages between adjacent stereocilia and microvilli are essential for mechanotransduction and maintaining their organization. They are anchored to actin through interaction of their cytoplasmic domains with related tripartite complexes consisting of a class VII myosin and adaptor proteins: Myo7a/SANS/Harmonin in stereocilia and Myo7b/ANKS4B/Harmonin in microvilli. Here, we determine high-resolution structures of Myo7a and Myo7b C-terminal MyTH4-FERM domain (MF2) and unveil how they recognize harmonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 70 publications
0
68
0
3
Order By: Relevance
“…Of note, the causative genes for three USH1 subtypes (USH1E, USH1K and USH1H) still have not been identified, suggesting that more Usher complex components may remain to be discovered (17)(18)(19). A similar situation is seen with the IMAC; structure-function studies of this complex clearly point towards the idea that the full interactome is not yet known (5,20,21).…”
Section: Introductionmentioning
confidence: 93%
“…Of note, the causative genes for three USH1 subtypes (USH1E, USH1K and USH1H) still have not been identified, suggesting that more Usher complex components may remain to be discovered (17)(18)(19). A similar situation is seen with the IMAC; structure-function studies of this complex clearly point towards the idea that the full interactome is not yet known (5,20,21).…”
Section: Introductionmentioning
confidence: 93%
“…1B). Here, heterotypic extracellular linkages occur near the tips of microvilli between protocadherin PCDH24 (encoded by CDHR2) and mucin-like protocadherin MLPCDH (encoded by CDHR5) to form links of 50 nm width (Crawley et al, 2014a(Crawley et al, , 2016Li et al, 2016;Yu et al, 2017). The cytoplasmic tail of PCDH24 binds USH1C (harmonin) and forms a ternary linkage with the SANS homolog ANKS4B to link to the MyTH4-FERM domains of Myo7b.…”
Section: Apical Membrane Morphology: the Cell Polarity Program And Mementioning
confidence: 99%
“…Immunostaining studies showed that Myosin VIIA (MYO7A), USH1G (also known as Sans), and USH1C (also known as Harmonin or autoimmune enteropathy-related 75-kDa antigen ) are located at the UTLD, suggesting that they are involved in the electron-dense plaque formation, although the mechanism underlying the dense assembly formation is not understood (Grati and Kachar, 2011;Grillet et al, 2009). MYO7A, USH1G, and USH1C form a very stable tripartite complex via several pairs of specific interactions (Adato et al, 2005;Li et al, 2017;Pan and Zhang, 2012;Wu et al, 2011;Yan et al, 2010;Yu et al, 2017). The cytoplasmic tail (CT) of CDH23 interacts with USH1C (Pan et al, 2009;Siemens et al, 2002), thus linking the tail of the upper tip-link to UTLD ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The cadherin-related family member 2 (CDHR2, also known as protocadherin 24) and cadherin-related family member 5 (CDHR5, also known as mucin-like protocadherin) interact in trans to form the filamentous tip-link (Crawley et al, 2014b). The CT of CDHR2 is coupled to the actin filaments via a tripartite complex composed of Myosin VIIB (MYO7B), USH1C, and ANKS4B (Crawley et al, 2014b(Crawley et al, , 2016Li et al, 2016aLi et al, , 2017Weck et al, 2016;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%